The potential for biochar application in “Shatangju” (Citrus reticulate cv.) orchard on acid red soil: Biochar prepared from its organic waste in an orchard - Guo, Yanjun; Qiu, Baoli; Khan, Zaid; Jiang, Hui; Ji, Qianhua; Fan, Qizhou; Khan, Muhammad Musa (Frontiers in Plant Science, 2022)
Carbonization of agricultural and forestry wastes is the main use of biochar application in agriculture. In this study, the effects of biochar on the physical and chemical properties of soil and diversity in rhizosphere microorganisms, leaf nutrients and fruit quality of acid red soil in “Shatangju” (Citrus reticulate cv.) orchard were studied using organic wastes and small-scale carbonization furnaces from orchards were used to produce biochar. The results showed that the finished rate of biochar produced from the organic wastes in the orchard was approximately 37%, and the carbon content of the finished product was as high as 80%. The results suggested that the biochar produced in the orchard could meet the annual consumption of the orchard. Applying biochar can improve the physical and chemical properties of acid soil in the “Shatangju” orchard by enhancing the availability of various mineral nutrients such as nitrogen, phosphorus, potassium, calcium, magnesium and boron. The species and quantity of root and rhizosphere microbial communities (fungi, bacteria and archaea) increased, and the dominant bacterial group changed, manifested in the increase in microbial diversity. Biochar directly affected the soil pH value and increased the soil organic carbon content, which may be the main reason for the change in microbial diversity in the soil and rhizosphere of “Shatangju” in the orchard and pot tests. The fruit quality of each treatment group with biochar was also better than that of the control group and improved fruit coloring. In the pure soil test, whether or not chemical fertilizer was applied, 3% biochar amendments can provide a suitable pH value for “Shatangju” growth and are relatively stable. Regardless of whether or not fertilizer was applied, 1.5%-3% biochar improved the soil in the pot test. In the field, the biochar at a rate of 2.4 kg/plant to 3.6 kg/plant, respectively, was the best in improving soil physical and chemical properties, foliar nutrition and fruit quality. Therefore, the amount of biochar added in the open environment (if the garden) can be slightly adjusted according to the results of the closed environment test (pure soil test and pot test). In this experiment, we explored the self-recycling of organic carbon, mainly through the preparation of a simple small-scale biochar furnace suitable for the use by orchards, and selected the appropriate amount of biochar to improve the physical and chemical conditions of “Shatangju” orchard soil and increase fruit quality.